The Existence of State Constitutional Incarnation on the Expansion of Corporate Criminal Liability in Indonesia - Utari Debora; Yasmirah Mandasari Saragih; Frenki Hamonangan Turnip; Nora Elida Manurung; Gunawan Putra Manihuruk (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2024)
The development of corporate criminal law shows a paradigm shift from individual to collective legal subjects, including legal entities. The Constitution as a fundamental norm in the Indonesian legal system becomes the main foundation in legitimizing the expansion of criminal liability of corporations. This research aims to analyze how the incarnation of the state constitution is present in strengthening corporate criminal liability, as well as assessing the effectiveness of existing regulations. By using a normative juridical approach, this research emphasizes the importance of harmony between the constitution and legislation in ensnaring corporate crimes. The results show that the recognition of corporations as subjects of criminal law is in line with constitutional values, although there are still weaknesses in the implementation of law enforcement.